Solusi Pemanfaatan Secara Optimal Limbah Pinang Dalam Upaya Peningkatan Produksi Tanaman Pinang Di Desa Jati Mulyo Secara Berkelanjutan: Solusi Pemanfaatan Secara Optimal Limbah Pinang dalam Upaya Peningkatan Produksi Tanaman Pinang di Desa Jati Mulyo Secara Berkelanjutan - Eva Achmad; Bambang Irawan; Fazriyas; Rike Puspitasari Tamin; Maria Ulfa (Altifani Journal: International Journal of Community Engagement, 2025)
Jati Mulyo Village is one of the villages in Dendang District, East Tanjung Jabung Regency, Jambi Province which is one of the areca nut and pineapple producing areas in Jambi Province. The productivity of areca nut produced is very good but until now areca nut waste has not been optimally processed by farmers. The low knowledge of farmers in processing areca nut waste into soil improver (compost) is an obstacle in the desire of farmers in processing areca nut waste. The purpose of this community service activity is to provide education and training to farmers about the utilisation of areca nut waste into compost as well as the utilisation of the compost to increase areca nut and pineapple production in Jati Mulyo Village. This community service activity includes counselling activities, demonstrations and training, mentoring and evaluation to partners to be able to use the science and technology in the management of areca nut waste.  This community service activity resulted in an increase in farmers' knowledge and skills in making compost made from the main raw material of areca nut waste.